Pengembangan Buku Suplemen Elektronik Materi: Sejarah Banjir dan Pembangunan Saluran Air di Tulungagung Tahun 1939-1986 Untuk Pembelajaran Sejarah Kelas X IIS 3 SMA Katolik ST. Thomas Aquino Tulungagung - Sukoco, Galih Fajar (UIN Raden Mas Said Surakarta, 2021)
Technology has been growing and has also penetrated into the field of education. Theuse of technology in the field of education is now being intensively promoted to facilitate thelearning process, as well as in learning history. This research and development aims to produceteaching materials in the form of an electronic Supplementary Book for the History of Floods andWaterways Construction in 1939-1986 in Tulungagung for students of class X IPS 3, SMA CatholicSt. Thomas Aquino Tulungagung. This teaching material is in the form of an E-book which wasdeveloped through the Anyflip application and Canva to achieve the desired final product. Themethod used is Sukmadinata's research and development model which initially has ten steps buthas been modified by the researcher into five steps. The results of this research and developmentshow that the validation of the material gets a value of 91.6%. While the media validation obtaineda value of 90% and the effectiveness test of teaching materials was 91%. From the overall results,it can be said that this Electronic Supplement Book teaching material product is very valid (worthy)to be used as supporting teaching materials in the process of learning history of specialization inthe classroom.